Clinical practice guidance for juvenile idiopathic arthritis (JIA) 2018. Issue 1 (2nd January 2019) - Okamoto, Nami; Yokota, Shumpei; Takei, Syuji; Okura, Yuka; Kubota, Tomohiro; Shimizu, Masaki; Nozawa, Tomo; Iwata, Naomi; Umebayashi, Hiroaki; Kinjo, Noriko; Kunishima, Tomoko; Yasumura, Junko; et al.
Abstract: Juvenile idiopathic arthritis (JIA) is the most common disease in pediatric rheumatism. There is no specific symptom or examination finding for JIA, and the diagnosis is made by exclusion and differentiation. Because non-pediatric rheumatologists are sometimes involved in medical care, 'proposal for JIA guidance on diagnosis and treatment for primary care pediatricians and non-pediatric rheumatologists' was first published in 2007. In these 10 years, a number of new findings on pathophysiology and treatment of JIA have been published; therefore, we propose this guidance of 2018th edition aiming at updating and standardization of JIA medical care in Japan. This edition included the management of uveitis, macrophage activation syndrome, infectious diseases before and during treatment. Moreover, details of biologics are also described. Although this guidance is tailored to adaptation of examinations and drugs, we do not purpose to limit the physicians' discretion in clinical practice. This guidance should be viewed as recommendations and be individualized according to the condition of the patient. We hope that medical care for JIA will advance and more patients will get benefit based on this guidance. Then, further revisions are needed due to changes in future conditions.